2012
DOI: 10.1155/2012/914196
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality among 2009 A/H1N1 Influenza Hospitalizations in Maricopa County, Arizona, April 2009 to March 2010

Abstract: We analyzed individual-level data on pandemic influenza A/H1N1pdm hospitalizations from the enhanced surveillance system of the Maricopa County Department of Public Health, AZ, USA from April 1st, 2009 to March 31st, 2010. We also assessed the the risk of death among A/H1N1 hospitalizations using multivariate logistic regression. Hospitalization rates were significantly higher among Native Americans (risk ratio (RR)  =  6.2; 95% CI: 6.15, 6.21), non-Hispanic Black (RR = 3.84; 95% CI: 3.8, 3.9), and Hispanics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…Risk of death among A/H1N1 influenza inpatients increased by a factor of 2.66 (95% CI: 2.11, 3.35) with admission delays >2 days after adjusting for other covariates, which is in line with previous studies [48], [49], [50], [51]. Overall the distribution of admission delays in our study is similar to that reported in other studies [50], [52], [53], [54].…”
Section: Discussionsupporting
confidence: 91%
“…Risk of death among A/H1N1 influenza inpatients increased by a factor of 2.66 (95% CI: 2.11, 3.35) with admission delays >2 days after adjusting for other covariates, which is in line with previous studies [48], [49], [50], [51]. Overall the distribution of admission delays in our study is similar to that reported in other studies [50], [52], [53], [54].…”
Section: Discussionsupporting
confidence: 91%
“…Further, rates of respiratory viral infections are higher for Apache Indians, Alaska Natives and Blacks than for NHWs 45 . These aforementioned differences align with the larger trend that influenza-associated pneumonia and pandemic influenza-related deaths are more common in racial and ethnic minority populations 16,40,46,47 .…”
Section: Elevated Risk For Severe Sars-cov-2 For Racial and Ethnic MIsupporting
confidence: 60%
“…For each county in our study, we compiled the total number of influenza hospitalizations over the study period and summaries of several county-level variables. From a non-exhaustive review of the literature, we identified potential confounders: insurance coverage, 12,13 number of primary care physicians per 100 000 population, 14,15 environmental humidity, 11,16 chronic disease and pregnancy rates, [17][18][19][20] percentage of the county population living below the poverty level, 12,21,22 vaccination uptake, [23][24][25] racial composition, [26][27][28][29] population density, 30,31 and prevalence of smoking. [32][33][34] A concise description of data sources and variable definitions for all covariates is provided in Table 1.…”
Section: Datamentioning
confidence: 99%